Health literacy and Health behaviors 3E-2S among Public Health Students in Kalasin University - Saiyasalee, Sonthaya; Sukserm, Thanoosin; Suwannarong, Bussakorn; Thammarakcharoen, Surasak; Sukmanee, Phannarai (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2025)
The study of health literacy and health behavior 3E-2S among public health students in Kalasin University was a cross-sectional descriptive study. The objective of the study was to examine the factors associated with health behavior 3E-2S of public health students at Kalasin University. The samples were 387 first- to fourth-year public health students. The data were collected in January 2024 using a questionnaire. Quantitative data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The chi-square test and Pearson’s correlation coefficient were used to test relationships. Results showed that the samples had a good overall level of health literacy (𝒙̅ = 50.83, SD = 5.86) and a good overall level of 3E-2S health behaviors (𝒙̅ = 21.18, SD = 3.28). When analyzing the relationship between health literacy and 3E-2S health behaviors, it was found that health information and service access, health communication, self-management, media and information literacy, and overall health literacy were significantly positively correlated with 3E-2S health behaviors (p < 0.001). Meanwhile, making appropriate decisions was also significantly positively correlated with 3E-2S health behaviors (p < 0.01). In addition, the samples had an inadequate level of health knowledge and understanding, and a fair level of health communication. Therefore, health literacy should be promoted among public health students in terms of health knowledge and understanding, as well as effective health communication. Integrating these elements into relevant curricula could enhance and develop their health literacy. This would enable them to effectively communicate health information to the public, helping individuals adopt correct and consistent health behaviors based on the 3E-2S framework.